F05 Mutant huntingtin fragmentation in immune cells tracks Huntington's disease progression. (29th August 2012) - Andre, R; Weiss, A; Träger, U; Grueninger, S; Farmer, R; Landles, C; Scahill, R; Lahiri, N; Haider, S; Macdonald, D; Frost, C; Bates, G; et al.
Abstract : Background: Therapeutic approaches to treat Huntington's disease by lowering mutant (m)HTT levels are expected to proceed to human trials, yet non-invasive quantification of mHTT is not currently possible. The peripheral immune system in neurodegenerative disease is becoming increasingly recognised as important and peripheral immune cells have been implicated in HD pathogenesis. However, HTT levels in these cells have not been quantified before. Aims: To quantify mutant and total HTT levels in peripheral immune cells isolated from HD patients, and to determine whether these levels track with disease progression. Methods: Monocytes, T cells and B cells were isolated by magnetic cell sorting from the peripheral blood mononuclear fraction of whole blood. They were subjected to a time-resolved Förster resonance energy transfer (TR-FRET) immunoassay to measure mutant and total HTT protein levels. Estimates were made of their association with disease burden scores and brain atrophy rates. Fragmentation of HTT in peripheral immunocytes was monitored by immunoprecipitation and western blot. Results: Mean mHTT levels in monocytes, T cells and B cells differed significantly between HD patients and controls, and between pre-manifest mutation carriers and those with clinical onset. Monocyte and T cell mHTT levels were significantly associated with disease burden scores and caudate atrophy rates in HD patients. Mutant HTT N-terminal fragments detected in HD monocytes may explain the progressive increase in mHTT levels in these cells. Conclusions: These findings indicate that quantification of mHTT in peripheral immune cells by TR-FRET holds significant promise as a non-invasive disease biomarker. That mHTT levels in such cells are associated with disease progression and brain atrophy rates indicates their potential relevance to pathogenic events in the CNS. Clinical trials in HD aiming to modulate mHTT levels may be enhanced by the application of such quantification.